Incivility and the use of systems thinking to promote healthy voluntary organisations. (1st July 2019) - Phillips, Janet M.; Stalter, Ann; Brodhead, Josette; Scardaville, Debra; Ruggiero, Jeanne; Wiggs, Carol; Winegardner, Sherri; Provencio, Robyn
Abstract : Incivility in voluntary organisations is critically burdensome on a global level, but there is a dearth of literature on how to contend with the problem. This paper provides a description and an evaluation of and reflection on a workshop conducted to propose an evidence-based systems awareness model (SAM) for volunteers in professional organisations to use in mitigating incivility. Implications of the SAM model for a culture of caring in the voluntary sector are described.